Language Attitudes of Students at Palembang Polytechnic of Tourism: Preserving National Identity Amid the Tide of Globalization - Trisna Rahmania; Nur Shabrina Reznani (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
The globalization era requires tourism vocational students to acquire proficiency in foreign languages as a fundamental competency for the hospitality industry. However, this increasing demand may influence their attitudes toward Indonesian as the national language. This study aims to analyze the language attitudes of students at Palembang Polytechnic of Tourism as an effort to preserve national identity amid the rapid expansion of globalization. Language attitudes are examined through three dimensions: cognitive, affective, and conative. This study employed a descriptive qualitative approach, with data collected through observations and semi-structured interviews involving students from various study programs selected using purposive sampling. The findings reveal a dual pattern of language attitudes among the students. From the cognitive and conative perspectives, students demonstrate a highly positive attitude toward English, primarily driven by instrumental motivation associated with broader employment opportunities in the global tourism industry. Nevertheless, from the affective perspective, students continue to express strong pride in Indonesian as an essential symbol of their cultural and national identity. The study concludes that implementing a proportional bilingual policy within higher education institutions is necessary to produce graduates who are globally competitive while maintaining their national identity.